Leviathan - Hobbes, Thomas, 1588-1679; Brooke, Christopher, 1973- ([Harmondsworth, Middlesex] : Penguin Books, 2017)
The renowned work by the English political philosopher examines the structure of society and legitimate government, arguing for a social contract and rule by an absolute sovereign.
""During the time men live without a common Power to keep them all in awe, they are in that condition which is called Warre." Written during the turmoil of the English Civil War, Leviathan is an ambitious and highly original work of political philosophy. Claiming that man's essential nature is competitive and selfish, Hobbes formulates the case for a powerful sovereign -- or "Leviathan" -- to enforce peace and the law, substituting security for the anarchic freedom he believed human beings would otherwise experience. This worldview shocked many of Hobbes's contemporaries, and his work was publicly burnt for sedition and blasphemy when it was first published. But in his rejection of Aristotle's view of man as a naturally social being, and in his painstaking analysis of the ways in which society can and should function, Hobbes opened up a whole new world of political science. Based on the original 1651 text, this edition incorporates Hobbes's own corrections, while also retaining the original spelling and punctuation, to read with vividness and clarity. C. B. Macpherson's introduction elucidates one of the most fascinating works of modern philosophy for the general reader." --
Part I Of Man -- Part II Of Common-wealth -- Part III Of a Christian Common-wealth -- Part IV Of the Kingdome of Darknesse -- A review, and conclusion.
First published in 1651.
Includes bibliographical references (pages 599-631).
English.
Keywords: Political science -- Early works to 1800.; State, The -- Early works to 1800.; PHILOSOPHY / Political; POLITICAL SCIENCE / History & Theory; POLITICAL SCIENCE / Political Process; Political science; State, The; Politics and Government; Early works